The parasitic impact of Romanomermis iyengari Welch (Nematoda: Mermithidae) on the survival and biology of the common mosquito, Culex pipiens L. (Diptera: Culicidae) - Elbrense, Hanaa; Shamseldean, Muhammad; Meshrif, Wesam; Seif, Amal (African Entomology, 2022)
The extensive use of chemical insecticides to control mosquitoes led to the development of insecticide resistance and environmental health hazards. This caused a surge in interest in eco-friendly biocontrol agents. The present study aimed to explore the susceptibility of different instar larvae of the common mosquito, Culex pipiens Linnaeus, 1758, to the mermithid nematode, Romanomermis iyengari Welch, 1964. Moreover, the effects of R. iyengari on the mosquito pupal developmental time, adult emergence, longevity, female fecundity, as well as egg-hatching rate were determined after larval treatment with an LC50 quantity of the nematode pre-parasites. Different instars of Cx. pipiens (1st–4th) were exposed separately to R. iyengari at concentrations of 1–6 pre-parasites/mosquito larva. Mortality rates of mosquito larvae were observed and the LC50 values were calculated. The estimated LC50 values for the 1st–4th larval instars were 3.18, 2.73, 3.79 and 4 pre-parasites/larva, respectively. Mean percent mortality of the 1st–4th larval instars ranged from 10–94%, 16–100%, 4–100% and 0–52%, respectively. The results indicated that exposure of 4th larval instar to the LC50 of R. iyengari pre-parasites significantly prolonged the duration of pupal development, reduced the percentage of emerged adults and reduced mosquito female fecundity compared with the control. In contrast, adult longevity and the egg-hatching rate did not differ between the control and the exposed group. In conclusion, this isolate of R. iyengari could be a promising biocontrol agent for Egyptian Cx. pipiens. Other trials are required to assess the biocontrol potential of this parasite in field conditions.